2017
DOI: 10.1002/ijgo.12127
|View full text |Cite
|
Sign up to set email alerts
|

Shock index and vital-sign reference ranges during the immediate postpartum period

Abstract: Specific reference ranges for patients during the postpartum period could be used in future studies to determine the parameters, or combinations of parameters, that perform best as early markers of hemodynamic compromise in women experiencing early postpartum hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 8 publications
0
19
1
2
Order By: Relevance
“…To our knowledge, the study is the first to prospectively determine the normal range of SI and other vital signs in the immediate postpartum period. Previous studies evaluating normal ranges of SI were either retrospective studies or a secondary analysis of prospective observational studies 12,15 ; in addition, some studies used time points beyond the first hour despite the WHO recommendation for adequate monitoring of postpartum women to commence within the first hour of delivery 16 . Furthermore, other studies derived the normal range of SI from populations in high‐income countries.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the study is the first to prospectively determine the normal range of SI and other vital signs in the immediate postpartum period. Previous studies evaluating normal ranges of SI were either retrospective studies or a secondary analysis of prospective observational studies 12,15 ; in addition, some studies used time points beyond the first hour despite the WHO recommendation for adequate monitoring of postpartum women to commence within the first hour of delivery 16 . Furthermore, other studies derived the normal range of SI from populations in high‐income countries.…”
Section: Discussionmentioning
confidence: 99%
“…This study is unique in that it is the first study to prospectively determine the normal range of shock index and other vital signs in the immediate postpartum period. Previous studies evaluating normal ranges of shock index were either retrospective studies or secondary analysis of prospective observational studies [12][13][14] and some have used time points beyond the first hour despite the World Health Organization recommendation on the need for adequate monitoring of postpartum women to commence within the first hour of birth [15]. In addition, this is the first study to evaluate normal ranges of shock index in a low-resource setting as values from other studies were derived from women in high income countries.…”
Section: Discussionmentioning
confidence: 99%
“…In the non‐pregnant population, a shock index > 1.0, thus a higher heart rate than systolic blood pressure measured at least once in the observation period, has been associated with morbidity and mortality in critically ill patients suffering trauma, sepsis and after surgery . A study among 8874 women without postpartum hemorrhage reported a range of 0.5 to 1.1 for the shock index immediately following delivery . Another study among 233 women with postpartum hemorrhage with blood loss exceeding 1500 mL concluded that a shock index ≥ 1.7 was a predictor of intensive care unit admission, invasive surgical procedures and transfusion of ≥ 4 units of packed red blood cells, with respective area under the curves 0.75 (95% confidence interval [CI] 0.63–0.87), 0.62 (0.45–0.79) and 0.67 (0.58–0.76) .…”
Section: Improving Maternal Outcomes: Timely Recognition Of Patients mentioning
confidence: 99%